2013
DOI: 10.4284/0038-4038-2011.207
|View full text |Cite
|
Sign up to set email alerts
|

Patentability and Knowledge Spillovers of Basic R&D

Abstract: This study develops an R&D-based growth model with basic and applied research to analyze the growth and welfare e¤ects of two patent instruments: (a) the patentability of basic R&D, and (b) the division of pro…t between basic and applied researchers.We …nd that for the purpose of stimulating basic R&D and economic growth simultaneously, increasing the share of pro…t assigned to basic researchers is more e¤ective than raising the patentability of basic R&D, which has either a negative e¤ect or an inverted-U e¤e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…The same argument has been suggested in different studies (Akcigit, Hanley, & Serrano-Velarde, 2013;Chu & Furukawa, 2013;Shapiro & Taylor, 2013), and Schumpeterian growth models also considered that basic research yields more knowledge spillovers, and, for this reason, it is particularly important for economic growth (Aghion & Howitt, 1996). Empirical analyses confirmed that large spillovers arise from basic research (Salter & Martin, 2001): Funk (2002) found that it generates much larger international spillovers; Griliches (1985), Mansfield (1980) and Lichtenberg and Siegel (1991) identified a "premium" for basic research, meaning that it is more important for productivity increase than other types of R&D; and Mansfield (1991) estimated a 28% social rate of return of academic research in the late 1970s.…”
Section: Randd and Knowledge Spilloverssupporting
confidence: 76%
“…The same argument has been suggested in different studies (Akcigit, Hanley, & Serrano-Velarde, 2013;Chu & Furukawa, 2013;Shapiro & Taylor, 2013), and Schumpeterian growth models also considered that basic research yields more knowledge spillovers, and, for this reason, it is particularly important for economic growth (Aghion & Howitt, 1996). Empirical analyses confirmed that large spillovers arise from basic research (Salter & Martin, 2001): Funk (2002) found that it generates much larger international spillovers; Griliches (1985), Mansfield (1980) and Lichtenberg and Siegel (1991) identified a "premium" for basic research, meaning that it is more important for productivity increase than other types of R&D; and Mansfield (1991) estimated a 28% social rate of return of academic research in the late 1970s.…”
Section: Randd and Knowledge Spilloverssupporting
confidence: 76%
“…However, in reality, private firms also conduct basic research, as stressed by the literature (e.g. Chu et al ., ; Chu and Furukawa, ; Cozzi and Galli, ). To discuss this issue, we extend the present model following Chu and Furukawa ().…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al, 2012;Chu and Furukawa, 2013;Cozzi and Galli, 2009, 2014. To discuss this issue, we extend the present model following Chu and Furukawa (2013). For simplicity, we assume that g = 0 and h = 0 in the production sector.…”
Section: Basic Research Funded By Private Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Bond and Zissimos (2010) demonstrate how the patent breadth can vary across identical countries. Chu and Furukawa (2011) study the optimal patentability and assigned profit share of basic R&D.…”
Section: Introductionmentioning
confidence: 99%